A report of visual impairment among children with disability/ Noor Halilah Buari and Noor Shuhada Aziz - Buari, Noor Halilah; Aziz, Noor Shuhada (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The visual impairment among children could interfere with visual development and affect the quality of life. Therefore, the status of visual impairment and its correlation with demographic, visual acuity and refractive error among disability children was investigated. A retrospective study was conducted to review the clinical records of children with disability (birth to 18 years old) from the Low Vision and Rehabilitation Clinic of UiTM Visioncare. The age, gender, types of disability and ocular parameters such as visual acuity and refractive errors were extracted and analysed. A total of 27 clinical records were reviewed. A total of 25.9% of children with a disability had a visual impairment. It was higher among boys (17.8%) than girls (7.41%). A strong positive linear correlation was exhibited between visual acuity and visual impairment (r=0.80, p=0.01). Meanwhile, the visual impairment was poorly correlated with gender, types of disabilities and refractive error. Thus, children with disability prone to have vision impairment. Visual acuity provides information on visual impairment status can be detected and measured in clinical setting. This report could help the clinician to be better prepared when dealing with children with any types of disabilities for early detection of visual disorder and better intervention prognosis.